2005
DOI: 10.2514/1.2176
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic System Development Using Proper Orthogonal Decomposition and Volterra Theory

Abstract: This research combines Volterra theory and proper orthogonal decomposition (POD) into a hybrid methodology for reduced-order modeling of aeroelastic systems. The outcome of the method is a set of linear ordinary differential equations (ODEs) describing the modal amplitudes associated with both the structural modes and the POD basis functions for the fluid. For this research, the structural modes are sine waves of varying frequency, and the Volterra-POD approach is applied to the fluid dynamics equations. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 15 publications
(12 reference statements)
0
25
0
Order By: Relevance
“…Gabbay et al (2000) and Mehner et al (2000) used polynomial functions whose coefficients were identified using strain energy data from a series of finite element runs, to model a microelectromechanical system. Silva et al have used a Volterra series approach to identify linear and nonlinear aerodynamic systems (Silva, 1997(Silva, , 1999Silva and Raveh, 2001;Silva and Bartels, 2002;Lucia et al, 2003). Denegri and Johnson (2001) have conducted a study based upon a neural network model using flight test data which has shown promise.…”
Section: Article In Pressmentioning
confidence: 97%
“…Gabbay et al (2000) and Mehner et al (2000) used polynomial functions whose coefficients were identified using strain energy data from a series of finite element runs, to model a microelectromechanical system. Silva et al have used a Volterra series approach to identify linear and nonlinear aerodynamic systems (Silva, 1997(Silva, , 1999Silva and Raveh, 2001;Silva and Bartels, 2002;Lucia et al, 2003). Denegri and Johnson (2001) have conducted a study based upon a neural network model using flight test data which has shown promise.…”
Section: Article In Pressmentioning
confidence: 97%
“…Detailed derivations of the POD and its properties are available elsewhere, and references and discussion are provided in recent review articles [3][4][5]16]. In our discussion of POD, N m basis vectors, or "modes" are used to represent deviations of x(t), an N f -dimensional vector, from a base solution, x 0 .…”
Section: The Proper Orthogonal Decomposition (Pod)mentioning
confidence: 99%
“…Much attention is currently being given to the efficient treatment of dynamic systems that develop simple LCO or more complicated dynamic responses. The authors have collaborated with NASA Langley Research Center to review the state-of-the-art in reduced order modeling and system identification techniques for aeroelasticity [3][4][5]. Methods reviewed include those based on the proper orthogonal decomposition (POD) (e.g., [3][4][5]), system identification with Volterra theory (e.g., [6]), harmonic balance (e.g., [7,8]), and a POD/Volterra hybrid strategy (e.g., [3][4][5]).…”
Section: Introductionmentioning
confidence: 99%
“…A topic of recent interest is the potential development of hybrid POD/Volterra methods. These hybrid techniques would combine the spatial resolution possible with POD methods with the low dimensionality and computational efficiency of Volterra methods [54,55].…”
Section: Introductionmentioning
confidence: 99%